DETERMINANTS OF CONVENTION SITE SELECTION IN THE CONTEXT OF MEETING ROOM IN HOTEL: AN ORGANIZERS’ PERSPECTIVE - ซุ้นสั้น นิมิต (RMUTT Global Business and Economics Review, 2018)
This study examines organizers’ perspective of selecting convention venue in the context of meeting rooms in hotel and investigates the causal relationships between the factors and loyalty. A total of 400 respondents completed a survey conducted on venue. Using multiple regression, the results of the analysis supported the proposed loyalty as follows: (1) there are four factors to select meeting room; facilities and safety, accessibility and support, location, and restaurant. (2) There are three factors; facilities and safety, accessibility and support, and location, had a significant and positive effect on loyalty. Managerial implications with regard to select meeting room are drawn based on the research findings, and suggestions for future researchers are presented.